2011
DOI: 10.1155/2011/172106
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing electroporation assisted silver nanoparticle delivery into living C666 cells for surface-enhanced Raman spectroscopy

Abstract: Abstract. Electroporation assisted metallic nanoparticle delivery has been shown by our previous work to significantly reduce the time of sample preparation for surface-enhanced Raman spectroscopy (SERS) measurements of biological cells. In this paper, we report our experimental work to optimize the electroporation parameters, including adjustment of the pulse pattern, operation temperature, and electroporation buffer, for fastest delivery of silver nanoparticles into living C666 cells (a human nasopharyngeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The potential of Raman spectroscopy for the analysis of effects of external agents (anticancer drugs, nanoparticles and CNT) on the cell has been demonstrated [21][22][23][24][25][26]. Candeloro et al reported the cytotoxic effects of Ag and Fe 3 O 4 nanoparticles on HeLa cells using Raman spectroscopy [27].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of Raman spectroscopy for the analysis of effects of external agents (anticancer drugs, nanoparticles and CNT) on the cell has been demonstrated [21][22][23][24][25][26]. Candeloro et al reported the cytotoxic effects of Ag and Fe 3 O 4 nanoparticles on HeLa cells using Raman spectroscopy [27].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, in presence of metal NCs a severe cellular damage and toxicity was observed even at lowest achievable electroporation parameters, single pulse of 1 ms with electric field strength of 0.5 kV cm −1  24. Thus, optimization of electroporation to achieve efficient intracellular delivery of a therapeutic cargo is challenging but critical and immediately required2627.…”
mentioning
confidence: 99%
“…In some Raman experiments, nanoparticle injection was chosen to administer metal nanoparticles into cells for SERS experiments, to avoid interaction of the nanoparticles with components of the cell culture medium and to achieve direct targeting of the cytosol [37], or to reach one specific cell [38]. Others have used electroporation for the direct uptake of nanoparticles [39][40][41].…”
Section: Probing Intrinsic Cellular Biochemistry With Sers Nanoprobesmentioning
confidence: 99%